PREVALENCE OF VANCOMYCIN RESISTANT ENTEROCOCCI FROM URINARY TRACT INFECTED PATIENTS - P. M., ARPITHA; RANI N., RAKSHITHA; K., SUMANA (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Urinary tract infections (UTIs) are one of the infectious diseases affecting humankind. The microbial agents that infect the tissues of the urinary tract from the renal cortex to the urethral meatus Enterococci are opportunistic pathogens that are found in the normal gut flora. Enterococci are the second leading cause of UTIs, accounting for 10% of all nosocomial UTIs. This species has become a major pathogen in the United States, Iran, Europe, and other parts of the world, including India. Antibiotic resistance is increasing, which slows the rate of progress in practical therapies, making susceptibility testing necessary. So, enterococci were isolated from urine samples of patients with UTI that were subjected to morphological characterization, biochemical assays, etc., The main aim of the study was to help in identifying resistance patterns and the dispersal of Enterococcus strains from various samples of urine to antibiotic agents like Penicillin G, Tetracycline, Teicoplanin, Norfloxacin, high-level Gentamycin, Linezolid, Nitrofurantoin, and with special emphasis on Vancomycin antibiotic. The greatest threat posed by Vancomycin-Resistant Enterococci (VRE) is its ability to transfer resistance genes to more dangerous gram-positive bacteria, potentially leading to truly terrifying pathogens in the future. A long stay in the hospital and the use of Vancomycin were connected to VRE-UTI and colonisation. Renal dialysis, renal failure, previous aminoglycoside, and third-generation cephalosporin use were all relevant hazard factors for VRE from UTI. The paper also underlines the importance of screening clinical samples for VRE and proposes that control measures be implemented to limit the spread of VRE.